2009
DOI: 10.1108/14777260910942579
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy career deciding: making choice a “good fit”

Abstract: A qualitative study like this can illustrate how career deciding occurs and provide insight into the process from a student's perspective. This can help inform guidance processes, selection to healthcare professions courses within the higher education sector, and stimulate debate amongst those involved with recruitment of healthcare workers about desirable motivators for healthcare careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Interestingly, the study found that dissatisfaction with career decision was prevalent amongst students who chose pharmacy due to pragmatic reasons such as high income, or those who sought alternative career pathways such as health policy or medicine/dentistry. Previous research has highlighted that those who undertake pharmacy study not as a final career destination and have alternate degrees such as medicine in mind, are less satisfied with their career choice and thus continue to plan exit avenues into other careers 20,34. Further research is required to test the likelihood of these students staying in pharmacy for a better understanding of workforce retention.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the study found that dissatisfaction with career decision was prevalent amongst students who chose pharmacy due to pragmatic reasons such as high income, or those who sought alternative career pathways such as health policy or medicine/dentistry. Previous research has highlighted that those who undertake pharmacy study not as a final career destination and have alternate degrees such as medicine in mind, are less satisfied with their career choice and thus continue to plan exit avenues into other careers 20,34. Further research is required to test the likelihood of these students staying in pharmacy for a better understanding of workforce retention.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly their socio-economic status and the type of health care systems all over the world 9 . Also, pharmacy students' undergraduate curriculum and their experiences in the final year of their graduate study can be an impact on their decisions 10 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, despite making curriculum changes to support the development of patient-centred pharmacists, there are a number of studies which suggest that graduates are unable (or find it difficult) to enact patient-centred ways of being a pharmacist 7,8. Health professional education (including medicine and nursing) and other professions (e.g.…”
Section: Introductionmentioning
confidence: 99%